IMPROVING THE TERRITORIAL COMPOSITION OF LAND USE BASED ON ASSESSMENT OF THE ECOLOGICAL AND ECONOMIC SITUATION (Scientific journal of the Fergana State University, 2024)
The assessment of the ecological and economic state is carried out on the basis of an analysis of the land use structure. With this approach to assessment, coefficients are calculated (Кмэз, Кнэз and Ктҳ), which make it possible to determine the level of tension in the environmental and economic situation. The article gives a brief overview of the essence of the concept of environmental-economic balance and methodological approaches used by various researchers to assess the anthropogenic load. Based on the results of the assessment of the environmental and economic balance, the importance of the recommendations and measures taken to normalize the anthropogenic load in the region was studied.